ETLINGERA TJIASMANTOI (ZINGIBERACEAE), A NEW SPECIES FROM CENTRAL SULAWESI - Marlina Ardiyani; Wisnu Handoyo Ardi; Wahyudi Santoso; Axel Dalberg Poulsen (Research Center for Biology, 2020)
ARDIYANI, M., ARDI, W. H., SANTOSO, W. & POULSEN, A. D. 2020. Etlingera tjiasmantoi (Zingiberaceae), a new species from Central Sulawesi. Reinwardtia 19(2): 103‒108. ‒‒ A new species of Etlingera, Etlingera tjiasmantoi Ardiyani & Ardi, was discovered at Tentena, Central Sulawesi, and is described here. This species resembles Etlingera flexuosa A.D.Poulsen and Etlingera mamasarum A.D.Poulsen & Ardiyani but differs from both in having thecae dehiscing through their entire length and in the obovoid, glabrous and spineless fruits. The DNA barcode data, the line drawings of flower and fruit and the plate of E. tjiasmantoi were presented.